Design approach for solar cell and battery of a persistent solar powered GPS tracker - Sahraei, Nasim; Watson, Sterling M.; Pennes, Anthony; Peters, Ian Marius; Buonassisi, Tonio (Japanese Journal of Applied Physics, 2017)
Sensors with wireless communication can be powered by photovoltaic (PV) devices. However, using solar power requires thoughtful design of the power system, as well as a careful management of the power consumption, especially for devices with cellular communication (because of their higher power consumption). A design approach can minimize system size, weight, and/or cost, while maximizing device performance (data transmission rate and persistence). In this contribution, we describe our design approach for a small form-factor, solar-powered GPS tracker with cellular communication. We evaluate the power consumption of the device in different stages of operation. Combining measured power consumption and the calculated energy-yield of a solar cell, we estimate the battery capacity and solar cell area required for 5 years of continuous operation. We evaluate trade-offs between PV and battery size by simulating the battery state of charge. The data show a trade-off between battery capacity and solar-cell area for given target data transmission rate and persistence. We use this analysis to determine the combination of solar panel area and battery capacity for a given application and the data transmission rate that results in minimum cost or total weight of the system.
CRIS-Team Scopus Importer:2022-06-05